The Effect of Medical Students' Moral Identity on Their Predisposition to Ethical Values - Ruhuşen Kutlu; Fatma Gökşin Cihan; Nazan Karaoğlu; Nur Demirbaş (Journal of Medical Education and Family Medicine)
Objective: The aim of this study was to investigate the relationships between medical students’ predispositions toward ethical values and moral identity and the sociodemographic factors affecting these predispositions.Methods: The population of this descriptive study consisted of first-year medical faculty students. The participants were administered the sociodemographic information form prepared by the researchers, the Disposition to Ethical Values Scale (EVPS) and the Moral Identity Scale (MIS).Results: The mean age of the 151 medical students who participated in the study was 18.9±0.9 years. There was no statistically significant relationship between the sociodemographic characteristics of the participants and the mean scores of the internalization and symbolization subscales of the MIS (P > .05). The mean score of the justice-honesty subscale (21.4±3.2) of students whose income was less than their expenses was higher than that of those whose income was equal to their expenses (18.1±4.2) and greater than their expenses (20.0±3.6). The mean score of the cooperation subscale (10.9±2.5) of the students whose mother's education level was high school and below was higher than that of the students whose mother was a university graduate (10.1±2.4). A significant positive correlation between the MIS and EVPS was found (r=0.226, P = .005).Conclusions: The levels of ethical sensitivity and moral identity of the medical students in this study were above average. Ethical sensitivity and moral identity were not influenced by sociodemographic variables. Ones who have greater moral identity are also more sensitive to ethics.